Transcriptome analysis of strawberry fruit in response to exogenous arginine - Lv, Jinhua; Pang, Qianqian; Chen, Xueqin; Li, Teng; Fang, Jinggui; Lin, Shaoyan; Jia, Haifeng (Planta, 2020)
Main conclusion Transcriptome and physiological analysis showed that exogenous arginine can delay the ripening process of postharvest strawberry fruit. Arginine (Arg) plays an important role in the growth and development of plants, but its growth and development regulatory mechanisms in strawberry fruit are unknown. In this study, we found that the content of Arg decreased after the onset of fruit coloration and exogenous Arg inhibited fruit coloration. We comprehensively analyzed the transcriptome of ‘Sweet Charlie’ strawberry fruit with or without Arg treatment and identified a large number of differential genes and metabolites. Based on the transcriptome data, we also found that Arg inhibited ripening, which coincided with changes in several physiological parameters and their corresponding gene transcripts, including firmness, anthocyanin content, sugar content, Arg content, indole-acetic acid (IAA) content, abscisic acid (ABA) content, and ethylene emissions. We also found that Arg induced the expression of heat-shock proteins (HSPs) and antioxidant enzyme genes, which improved strawberry stress resistance. This study elucidated the molecular mechanism by which exogenous Arg delays strawberry fruit ripening, providing some genetic information to help guide the future improvement and cultivation of strawberry.